Exquisite Textiles Sensors and Wireless Sensor Network Device for Home Health Care - Huang, Wen-Tzeng; Chen, Chin-Hsing; Chang, Yuan-Jen; Chen, You-Yin; Huang, Jung-Lin; Yang, Chang Ming; Yang, Tzu Lin (My University, 2008)
In this study, we propose a wearing system with four sensors, ECG (electrocardiogram), three-axis accelerometer, temperature, and tight-switch, applied for remote monitoring system in home-care. The sensors ECG, measured with wearable electrodes made of the steel textile to generate the real-time heart-rate estimator, tight-switch, made of the steel textile to check whether wearing person dresses properly, accelerometer, and temperature parameters are received via the ZigBee receiver within an exquisite belt. Since the movable textile electrodes will cause of unfixed contacts when the wearing person is in motion, making the heart-rate estimation much a sophisticated work, the tight-switch sensor and FIR (Filter Impulse Response) filter technology are applied here to get the more satisfiable heart-rate. The other two bio-sensors can detect the whether fall-down or not and normal body-temperature of this wearing person. Moreover, the ZigBee device with small size, low-power consumption, and high-reliability characteristics is designed to transmit the detected bio-information from these four sensors. Therefore, the vital system embedded with the capability of real-time heart-rate estimation and transmission makes it highly suitable for applications of remote healthcare and wellness.